Loading and velocity generation in the high performance tennis serve - Reid, M. (Medicine and Science in Tennis, 2008)
Shoulder injuries rank among the most prevalent and debilitating injuries sustained by professional tennis players. The loads endured by the tissues of the shoulder during stroke production, and more particularly the serve, are commonly implicated in shoulder joint injury.1-3 Indeed, past evidence points to these loads increasing along with serve velocity, as well as with varied segment use.4 The aim of this thesis was to therefore quantify how different types of serves (i.e. the flat serve and the kick serve) and how different service techniques (i.e. the foot-up) affected shoulder joint loading among high performance able-bodied and wheelchair players. Exciting in that it represented an opportunity for three-dimensional (3D) stereophotogrammetry - the gold standard in motion analysis - to evaluate a tennis stroke, and, challenging as the shoulder represents something of a `Holy Grail` in upper-limb biomechanics.